114k views
4 votes
I need urgent help please

I need urgent help please-example-1
User Jodonnell
by
4.7k points

2 Answers

7 votes

Answer:

see explanation

Explanation:

To evaluate f(- x) substitute x = - x into f(x)

f(- x) = (- x)² = x² = f(x) ← circle this one

f(- x) = (- x)³ = - x³ ≠ f(x)

f(- x) = sin(- x) = - sinx ≠ f(x)

f(- x) = cos(- x) = cosx = f(x) ← circle this one



User Ewooycom
by
5.0k points
7 votes

Answer:

circle 1st and last function.

Explanation:

f(x)=x²

replace x by -x

f(-x)=(-x)²

f(-x)=x²

hence f(x)=f(-x)=x² hence circle this one.

Now f(x)=x³

replace x by -x,we get

f(-x)=(-x)³

f(-x)=-x³≠f(x)

Now, f(x)=sinx

replace x by -x

f(-x)=sin(-x)=-sinx

f(x)≠f(-x)

Now,f(x)=cosx

replace x by -x

f(-x)=cos(-x)=cosx=f(x)

so,f(x)=f(-x). Also circle this one.

User Llimllib
by
5.2k points